Characteristics and outcomes of extracorporeal life support in pediatric trauma patients. Issue 4 (October 2020) - Behr, Christopher A.; Strotmeyer, Stephen J.; Swol, Justyna; Gaines, Barbara A.
Abstract : BACKGROUND: Extracorporeal life support utilizing extracorporeal membrane oxygenation (ECMO) techniques has been used in the pediatric population for numerous indications, but its use in trauma has been understudied. We sought to examine the indications, characteristics, and outcomes of children placed on ECMO for trauma and hypothesized that outcomes would be equivalent to those of patients placed on ECMO for other indications. METHODS: We performed a retrospective review of all pediatric trauma patients in the Extracorporeal Life Support Organization registry from 1989 to 2018. Patient characteristics, indications for ECMO, pre- and post-ECMO ventilator settings and blood chemistry, complications, and survival rates were examined. Categories were stratified by mode: venovenous (VV), veno-arterial (VA), or conversion. Data were analyzed using SPSS software, with significance considered at p value less than 0.05. RESULTS: We identified 573 patients with a median age of 4.82 years. The majority of patients (62.3%) were male and on VA support (54.5%). Drowning (38.7%) was the most common mechanism, followed by burns (21.1%) and thoracic trauma (17.8%). Complication rates were high (81.9%), with the most frequent types being cardiovascular, mechanical, and hemorrhagic. Incidences of complications (overall and by type) were similar to those reported in other Extracorporeal Life Support Organization cohorts. Overall survival was 55.3% and was significantly higher ( p = 0.00) for patients on VV (74.3%) compared with those on VA (41.7%), even when controlling for mechanism. CONCLUSION: Survival and complication rates of pediatric trauma patients on ECMO are comparable to those reported for other indications. Trauma should not be considered a contraindication for ECMO. LEVEL OF EVIDENCE: Therapeutic, level V. Abstract : Supplemental digital content is available in the text.